PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN SRAGEN - Kurniawan, Hutomo; Aji, Ambyah Atas (Widya Dharma Journal of Business - WIJoB, 2022)
This study aimed to determine work motivation, work discipline, and job satisfaction for the performance of district service employees partially and simultaneously. This study used a sample of 40 respondents. The sampling technique used is jenuh sampling or census where the sampling technique that takes all members of the population as a sample. A questionnaire is an instrument used to collect data. The test data in this study are validity, reliability, multiple linear analysis of the f test, t test and coefficient of determination. The data is processed using SPSS version 16. The results of the study found tcount > ttable calculation (4,150 > 2,028) and a significant value of 0.000 < 0.05. This means that work motivation has a positive and significant effect on the performance of District Service employees. tcount work discipline calculation > ttabel (4,887 > 2,028) and a significant value of 0.000 < 0.05. This means that work discipline has a positive and significant effect on the performance of District Service employees. thitung job satisfaction known to > ttabel (2,328 > 2,028) and a significant value of 0.022 < 0.05. This means that job satisfaction has a positive and significant effect on the performance of District Service employees. It is proven by the results of the F test that the F-value of the Fcount > Ftabel (125,053 > 2.84) and a significant value of 0.000 < 0.05 means that motivation, discipline and work satisfaction together have a positive and significant influence on the performance of district office employees.